Analysis of V–P–T relationships and bulk modulus for some geophysically-relevant solids using the Grover–Saxena equation of state. (November 2019) - Anand, K.; Singh, M.P.; Sharma, B.S.
Abstract: We use a simple method based on the Grover–Saxena equation of state (EOS) for investigating the volume–pressure–temperature (V–P–T) relationships and bulk modulus of NaCl, MgO, hcp iron, MgSiO3 and CaSiO3 perovskites. The effect of temperature is taken into account in terms of thermal pressure based on the Anderson formula. The results for volumes as a function of pressure and temperature present close agreement with available experimental data based on X-ray diffraction measurements and molecular dynamics simulations. The results determined from the Grover–Saxena EOS compare well with those from the Birch–Murnaghan EOS and the Vinet EOS. In the case of MgO, the comparison of V–P–T results is presented with the ab initio values reported recently by Belmonte (Minerals, 7 (2017) 183). The V–P–T relationship for hcp iron based on the Grover–Saxena EOS is used to predict the density and bulk modulus at the inner core boundary of the earth's interior, showing good agreement with seismic data. Highlights: Results are obtained for some geophysically relevant solids. The Grover–Saxena equation compares well with other equations of state. The ab initio results for MgO support the Grover–Saxena equation. Seismic results for the earth's inner core boundary are reproduced. Results for NaCl, MgSiO3 and CaSiO3 are close to experimental data.